2019
DOI: 10.1590/1678-992x-2018-0084
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of water status and iron deficiency chlorosis on grape composition in non-irrigated vineyards

Abstract: Although water deficit and iron deficiency chlorosis are common environmental stresses in the Mediterranean area, few data are reported in the literature on their effects on vineyards, when acting simultaneously. The main objective of this research was to study the combined effects of iron deficiency and water status on vigor, yield and fruit composition in rainfed vineyards. Moreover, the investigation aimed to evaluate the feasibility of using foliar chlorophyll content (Chl) and predawn leaf water potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 28 publications
2
15
0
1
Order By: Relevance
“…According to previous studies carried out in the same area (Hailemichael et al, 2016;González et al, 2019), no consistent correlations were obtained between Chl and LWP in 2016 (r = 0.04, p > 0.05) and 2017 (r = 0.12, p > 0.05); therefore, both variables could be considered independent.…”
Section: Values Of Water Potential and Chlorophyll Contentmentioning
confidence: 73%
See 2 more Smart Citations
“…According to previous studies carried out in the same area (Hailemichael et al, 2016;González et al, 2019), no consistent correlations were obtained between Chl and LWP in 2016 (r = 0.04, p > 0.05) and 2017 (r = 0.12, p > 0.05); therefore, both variables could be considered independent.…”
Section: Values Of Water Potential and Chlorophyll Contentmentioning
confidence: 73%
“…Increases in TPC were associated to the incidence of iron deficiency, according to Bavaresco et al (2005) and González et al (2019). However, due to LWP × Chl interaction (Table 3), differences between low and high Chl values were detected (p < 0.05) only in subzones with better water status at veraison (1529 mg kg -1 versus 1180 mg kg -1 in 2016, 940 mg kg -1 versus 780 mg kg -1 in 2017).…”
Section: Free and Bound Aroma Compoundsmentioning
confidence: 90%
See 1 more Smart Citation
“…Each season, data on foliar chlorophyll (Chl) content, predawn leaf water potential (LWP), and leaf area index (LAI) were obtained in the study subzones at veraison stage, with 75% of coloured berries (23-24 August 2016 and 9-10 August 2017). Chl content per leaf area unit (μg cm −2 ) was obtained following González et al 12 from readings of a CL-01 portable colorimeter (Hansatech Instruments Ltd, King's Lynn, UK). Data were recorded from 30 leaves in each subzone, always choosing the fourth or fifth fully expanded leaf counting from the tip.…”
Section: Study Site Description and Field Data Collectionmentioning
confidence: 99%
“…10,11 Recent studies in Ribera del Duero Designation of Origin (Spain) have demonstrated that mild to moderate iron deficiency can improve the phenolic content and aromatic potential of Tempranillo grapes. 12,13 It would be interesting to study to what extent these improvements are transferred to the composition and sensory characteristics of the wine. To the best of our knowledge, there are currently no studies on how iron deficiency affects the chemical and sensory qualities of wine.…”
Section: Introductionmentioning
confidence: 99%